2021
DOI: 10.21608/jtcps.2021.79169.1064
|View full text |Cite
|
Sign up to set email alerts
|

Various Uses of Natural Plants Extracts for Functionalization Textile Based Materials

Abstract: T HE use of natural colors creates no problems for waste disposal and can provide naturally dyed fabrics. Dyes may be derived from natural resources since old times. And The revival of sustainable plant-based dyes now a day is becoming the demand for the global community in all fields.so in this review, we discuss the application of natural plant extracts such as peanutpod which usedin the dyeing of cotton fabric and using olive tree leaves and its extraction to dye cotton fabric and dyeing wool using henna ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…[8][9][10][11][12] It is also the process of mixing a design concept, one or more colours, and a substrate (usually textiles) with a natural or synthetic thickener, while applying a technique to correctly apply the colours. [4,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] The main objective of printing is to create colourful patterns with sharp borders on textile fabrics without any dye spilling beyond the design motif's borders. [27] Textile printing is defined as a regulated technique of colouring cloth in specific patterns or motifs by employing specialized printing techniques and machinery.…”
Section: Textile Printingmentioning
confidence: 99%
“…[8][9][10][11][12] It is also the process of mixing a design concept, one or more colours, and a substrate (usually textiles) with a natural or synthetic thickener, while applying a technique to correctly apply the colours. [4,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] The main objective of printing is to create colourful patterns with sharp borders on textile fabrics without any dye spilling beyond the design motif's borders. [27] Textile printing is defined as a regulated technique of colouring cloth in specific patterns or motifs by employing specialized printing techniques and machinery.…”
Section: Textile Printingmentioning
confidence: 99%
“…The treated fabrics' durability provides strong antibacterial activity against all pathogens tested after washing. [79] The treated textiles are more effective against gram-positive bacteria than gram-negative bacteria because the cell walls of both tested bacterial strains differ in composition. Ergosterol, a crucial component of the fungal cell membrane, is likewise blocked by the polycations used.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…Recent studies have revealed that, in addition to natural textile materials, they may also be used to colour manufactured fibres. [19][20][21][22][23][24] They also have been found to have excellent ecological advantages, but their extraction yield is limited, and their fastness qualities are also unsatisfactory. [25][26][27][28] Researchers are attempting to overcome these two disadvantages by using some modifications for enhancing the colour strength of naturally dyed fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] The use of natural dyes is seen to be a preferable alternative to synthetic colours. [19][20][21][22][23][24][25][26][27].…”
Section: Natural Dyesmentioning
confidence: 99%
“…[10] They may be used to colour nearly all natural textiles. [2,25,34] Plants have historically been utilized to derive the bulk of natural colours. [7] The majority of natural colouring supplies include roots, leaves, stems, bark, wood shavings, flowers, fruits, rinds, hulls, husks, and other plant components.…”
Section: Natural Dyesmentioning
confidence: 99%